2021
DOI: 10.1177/10497323211008848
|View full text |Cite
|
Sign up to set email alerts
|

Mobility—A Bridge to Sense of Coherence in Everyday Life: Older Patients’ Experiences of Participation in an Exercise Program During the First 3 Weeks After Hip Fracture Surgery

Abstract: Our aim with this article was to explore the experiences of older people who participated in the evidence-based High-Intensity Functional Exercise (HIFE) Program during the first 3 weeks of rehabilitation after hip fracture surgery. Nineteen older people participated in the study. Data were analyzed using systematic text condensation. One overarching theme “Exercise is the key for regaining mobility and a sense of coherence (SOC) in everyday life” emerged from the analysis in addition to these five themes: (a)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…In other research studies, 2,39,40 as in this one, participants also reported yearning to return to their previous roles: physical, social and emotional, and the importance of physiotherapy and exercise. Some reported that they set personal goals according to the activities they wanted to be able to achieve; others suggested measuring and keeping daily recovery progress diaries.…”
Section: Discussionmentioning
confidence: 55%
See 2 more Smart Citations
“…In other research studies, 2,39,40 as in this one, participants also reported yearning to return to their previous roles: physical, social and emotional, and the importance of physiotherapy and exercise. Some reported that they set personal goals according to the activities they wanted to be able to achieve; others suggested measuring and keeping daily recovery progress diaries.…”
Section: Discussionmentioning
confidence: 55%
“…This was often done with emotions and a show of frustration. 39,41 Rehabilitation after HF is a dynamic process characterized by changes in the individual's physical and mental state. 41 Measuring PROs that are succinct but precise can help assess the required categories for clinical intervention in the rehabilitation process.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Her situation points to the problems with the overburdened health care system and the suffering it may cause to patients. Exercise is considered the key for regaining mobility after a hip fracture (Vestøl et al, 2021). The stories’ overall message is that a lot is at stake for the participants of this study.…”
Section: Discussionmentioning
confidence: 99%
“…The authors suggested individualised approaches taking the older adult´s physical, mental, as well as social conditions into account. Fortunately, participating in an individualised exercise programme, with improved mobility as a result, has been shown in a previous study to positively affect older adults’ self-image and be beneficial for social participation and identity [ 37 ]. Similar to our study, the participants in the latter study received exercise according to the High-Intensity Functional Exercise (HIFE) Program [ 38 , 39 ] in the early stage after the fracture.…”
Section: Discussionmentioning
confidence: 99%